Problematic Internet Use pada Remaja Pengguna Facebook di Jakarta Barat - Andangsari, Esther Widhi; Fitri, Rani Agias (Bina Nusantara University, 2014)
Paper discusses about problematic internet use on teenagers as Facebook users in West Jakarta. The objective of this study is to have empirical evidence about problematic internet use condition among teenagers as Facebook users in West Jakarta. This research is a descriptive study. Sample of this study was 82 high school students in West Jakarta. They were given GPIUS2 questionnaire constructed by Caplan. Result of the study is most of the teenagers have low score on problematic internet use especially in Facebook usage. The result is supported by the passiveness of Facebook online activity among the teenagers. However, there was a positive significant correlation between problematic internet use (PIU) and teenagers’ feeling when their smartphone was left behind at home. It means they could not access their Facebook account for some time. This result is important for parents and educators to consider, given that Facebook has both positive and negative effect for teenagers.